Alcohol-induced bone loss driven by dysregulated spatial distribution of gut microbiota and PGD2-IL17 pathway-mediated osteoclast activation - Guo, Haoyu; Bi, Yujing; Zhang, Gongzi; Luo, Shicheng; Jia, Xiaopeng; Yang, Ruifu; Peng, Ye; Zhang, Lihai (Frontiers in Microbiology, 2025)
IntroductionAlcohol-induced damage to bone microstructure leads to alcoholic osteoporosis (AOP). While prior studies have demonstrated alcohol’s negative impact on bone density, the mechanisms by which alcohol induces osteoporosis through immune pathways, gut microbiota dysbiosis, and metabolic alterations remain insufficiently characterized. Given that alcohol is primarily absorbed in the upper gastrointestinal tract, in this research, we aimed to elucidate the role of spatial distribution disorders in gut microbiota and metabolites in the pathogenesis of alcohol-induced osteoporosis. We further sought to evaluate the potential of microbiota supplementation and targeted immunosuppressants as therapeutic strategies for related bone diseases.MethodsAn osteoporosis model using mice was established using alcohol drinking bottles, and bone loss was validated using micro-computed tomography. Segmented intestinal samples and fecal samples were analyzed using 16S rRNA sequencing and metabolomics. Mechanistic studies were conducted by supplementing R. intestinalis, prostaglandin D2 (PGD2), and its specific immune inhibitor, ramatroban. Analytical methods included tartrate-resistant acid phosphatase staining, flow cytometry, and enzyme-linked immunosorbent assay.ResultsAlcohol disrupted the spatial complexity of intestinal segments and fecal microbiota in mice, causing metabolic dysregulation and ultimately leading to elevated PGD2 levels. This, in turn, triggered Th17/Treg immune imbalance and osteoclast activation, resulting in bone loss. Supplementation with the probiotic R. intestinalis or inhibition of PGD2 significantly improved bone density and alleviate inflammation.ConclusionThis study demonstrates that alcohol-induced elevation of PGD2 is a key pathogenic factor in AOP. PGD2 accelerates bone loss by promoting osteoclast formation through the activation of Th17 cells. Furthermore, this study highlights the importance of investigating the spatial distribution of gut microbiota and metabolites, providing potential targets and novel strategies for the precise treatment of AOP and other diseases associated with external stimuli.